Гледичія звичайна (Gleditsia triacanthos L.) в лісових культурценозах на південних чорноземах України - Derevyanko, V.M.; Levon, F.M. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 1999)
The results of periodic scientific observations of 1963–1999 on growth and condition of the honey-locust plantations in the Vladimirskiy wood stands of the Nikolaev region, learnt as the object of steppe afforestation are stated. The wood cultural cenoses of Gleditsia triacanthos (completely clean as to the structure, mixed, created according tree-shrubby type) differ by the highest stability and viability as compared with other plantations of the investigated forestland. Most aged clean gleditschia plantations created according the best ones of created according to tree-shrubby type in 1926. The average diameter of arbors there was 21.6 cm, height about 20.2 m at the age of 73. The perspective using of Gleditsia triacanthos as main and valuable concomitant arboreal specie for the oak under conditions of well-timed realization of patronizing forestry maintenance with the purpose of warning oppressing influencing of gleditschia on the oak in young age is emphasized. The strongly thorned form and lamelied bark form described by the authors are illustrated.